Components of Basic Childhood Vaccine Acceptance among Muslim Parents in the Yaha District Community, Yala Province - Jinarong, Taqwa; Vichitkunakorn, Polathep; Songwathana, Praneed (Princess of Naradhiwas University Journal, 2025)
This descriptive research aimed to investigate the components of basic childhood vaccine acceptance among Muslim parents in the community. The sample group consisted of 300 Muslim parents with children aged 0-5 years, selected through simple random sampling. The tool used a questionnaire on the components of childhood vaccine acceptance among parents, which had content validity index values of ≥ 0.75 for each item and 0.97 for the overall questionnaire. The Cronbach's alpha reliability coefficient was 0.91. Components were analyzed by using Exploratory Factor Analysis (EFA), extracted the components using Principal Component Analysis, and rotated the factor axes obliquely using the Varimax method. The research findings revealed that the components of basic childhood vaccine acceptance among Muslim parents in the Yaha district community of Yala province consisted of 5 components and 38 indicators. These included 1) Awareness and sources of information regarding vaccine production and safety with 18 indicators; 2) Vaccine efficacy and supporting evidence with 12 indicators; 3) Side effects of post-vaccination with 4 indicators; 4) Vaccine service system with 3 indicators; and 5) Halal vaccine with 1 indicator. Together, these 5 components and 38 indicators can explain 61.00% of the variance in the indicators, with eigenvalues of 15.83, 3.58, 1.53, 1.20, and 1.03, respectively. Therefore, primary healthcare services and the district network in the Yaha district should use the components and indicators as guidelines to promote vaccine coverage in the community. This includes proactive information management using role models and empirical evidence, ensuring the quality and halal status of vaccines, educating about side effects, and implementing an active vaccine service system.